Close-contact melting heat transfer on a heated horizontal plate: Revisited in the presence of nano-enhanced phase change materials (NePCM). (September 2018) - Hu, Nan; Zhu, Zi-Qin; Li, Zi-Rui; Tu, Jing; Fan, Li-Wu
Highlights: Close-contact melting heat transfer on a horizontal plate was revisited for NePCM. The measured melt fraction agrees well with a model for NePCM at various loadings. The 1 wt% NePCM has a higher melting rate than those of the blank and 3 wt% ones. Thickened melt film at higher viscosity is attributed to the slow-down of melting. The higher melting rate does not necessarily lead to a faster energy storage rate. Abstract: The classical problem of close-contact melting heat transfer on a heated horizontal plate was revisited experimentally in the presence of nano-enhanced phase change materials (NePCM), which were prepared by dispersing graphene nanoplatelets into 1-tetradecanol at loadings up to 3 wt%. The melting experiments were performed by measuring the instantaneous height, which represents the melt fraction, of a cylindrically-shaped solid NePCM sample placed vertically on a horizontal plate that was maintained at constant wall superheats. The measured variations of melt fraction were found to agree well with the predictions of a theoretical model, where the measured loading- and temperature-dependent effective thermophysical properties of the various NePCM samples were adopted for calculation. It was shown that melting can be accelerated by the 1 wt% sample. With further increasing the loading to 3 wt%, however, melting slows down due to the dramatic growth in viscosity. The thermal resistance across the melt film becomes higher as a result of the thickened film at the higher viscosity, which offsets the contribution of enhanced thermal conductivity. Due to the loss of heat storage capacity upon introduction of the nanoparticles, the higher melting rate was revealed to not necessarily lead to an improved heat storage rate.